2021
DOI: 10.1093/cid/ciab595
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Respiratory Syncytial Virus Infection Among Hospitalized Adults, 2017–2020

Abstract: Background Respiratory syncytial virus (RSV) infection causes acute respiratory illness and triggers exacerbations of cardiopulmonary disease. Estimates of RSV incidence in hospitalized adults range widely, and few data exist on incidence in adults with comorbidities that increase the risk of severe disease. We conducted a prospective, population-based, surveillance study to estimate incidence of RSV hospitalization among adults overall and those with specific comorbidities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 18 publications
5
98
2
Order By: Relevance
“…This was consistent with previously published data [19,[35][36][37] corroborating the leading role of hRSV in respiratory infections among younger children. However, in our series, nearly 5% were patients ≥50 years of age, thus exhibiting the impact of this virus also in adults and the elderly [38,39], which may consequently represent important targets for vaccination [40].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This was consistent with previously published data [19,[35][36][37] corroborating the leading role of hRSV in respiratory infections among younger children. However, in our series, nearly 5% were patients ≥50 years of age, thus exhibiting the impact of this virus also in adults and the elderly [38,39], which may consequently represent important targets for vaccination [40].…”
Section: Discussionmentioning
confidence: 65%
“…Modelling studies have shown greater rates of hospitalization due to hRSV in adults with high-risk conditions [49,50]. In this context, Prasad et al [38] in New Zealand and Branche et al [39] in USA reported significantly higher hRSV hospitalization rates among adults with chronic diseases affecting the cardiovascular system, or chronic obstructive pulmonary disease, diabetes, or end-stage renal disease, as compared with adults of similar age without each corresponding condition. Nevertheless, to the best of our knowledge, there are still no data that recognized any potential difference in the prevalence of specific hRSV subgroups and the presence of underlying medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no licensed RSV vaccines. The burden of disease in older adults is substantial, and in the USA, 137 to 256 hospitalized RSV cases have been reported per 100,000 population in ≥65-years old ( Branche et al, 2021 ). Efficacy and immunogenicity data were presented for an adenovirus-based RSV vaccine in a randomized, double-blind, placebo-controlled Phase 2b trial in patients aged ≥65 years old (CYPRESS (NCT03982199)).…”
Section: Short Presentations: Preventionmentioning
confidence: 99%
“…6 Patient-level cost data from prospective studies in which all suspect RSV cases are tested and ascertainment of RSV is complete could reduce bias and improve generalizability, but there are no published data using this approach. We designed a nested study within a large, prospective, multi-center, multi-season, populationbased, active surveillance study of RSV-associated hospitalization in adults ≥ 18 years of age 4 and collected epidemiologic and cost data, to estimate the cost of RSV-associated hospitalizations and determine factors associated with higher costs.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) causes upper and lower respiratory tract infections, with severe disease primarily in infants and older adults. The annual burden of RSV in adults in the United States is high, with an estimated 600,000–1,000,000 medically attended visits, 1 , 2 , 3 130,000–177,000 hospitalizations, 3 , 4 and 11,000–17,000 deaths 3 , 5 , 6 , 7 , 8 resulting in substantial healthcare resource utilization and cost.…”
Section: Introductionmentioning
confidence: 99%